Inclusions in magnesium and its alloys: a review. (September 2013) - Lun Sin, S.; Elsayed, A.; Ravindran, C.
Abstract : High volume application of lightweight materials is the key to improving fuel efficiency and vehicle performance, and decreasing exhaust emissions to address environmental concerns. Currently, magnesium alloys, which are the lightest structural materials, represent only ∼0·3% of an automobile weight. One of the most important parameters in controlling the properties of magnesium and its alloys is melt cleanliness, manifested mainly in inclusions. The presence of such inclusions will strongly influence the mechanical properties and corrosion resistance of structural components. This paper gives an overview of the current state of knowledge pertaining to magnesium melt cleanliness. It describes the nature and origin of the inclusions, the methods for assessing the cleanliness of magnesium, the methods used to control inclusions in the melt and the relationship between melt cleanliness and the properties of magnesium castings.